상악에 발생한 뮤코르 진균증의 치험례 - 김여갑(Yeo-Gab Kim); 김주동(Ju-Dong Kim); 류동목(Dong-Mok Ryu); 이백수(Baek-Soo Lee); 오정환(Jung-Hwan Oh) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2004)
Mucormycosis is an acute opportunistic infection caused by a saprophytic fungus found in soil, decaying fruits and vegetables. Numerous predisposing risk factors are associated with mucormycosis, although most cases have been reported in poorly controlled diabetics or in patients with hematologic malignant conditions. Throughout the history of mucormycosis, from the first case in humans reported in 1885 by Paltauf, through publication by Gregory et al of the first observation of rhino-orbital cerebral mucormycosis in 1943, to the report by Harris in 1955 of the first known survivor, little has changed in the diagnosis and outcome of this disease. Without treatment, the patient may die after an interval ranging from a few days to a few weeks. Regulation of diabetes mellitus and a decrease in the dose of immunosuppressive drugs facilitate the treatment of Mucormycosis. Extensive debridement of craniofacial lesions appears to be very important. intravenous amphotericin B is clearly of value. This is a case report of a patient with mucormycosis in maxilla. He was an uncontrolled DM patient, and for the treatment of intravenous amphotericin B and sequestrectomy were applied. KCI Citation Count: 2